Efektifitas Pemberian Intervensi Terapi Bekam Terhadap Penurunan Tingkat Nyeri Pada Pasien Dengan Gout Arthritis Di Praktek Mandiri Perawat Dawan Usadha - Widiani Sari, Kadek; Pratama, Aditha Angga; Martini, Made (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Gout arthritis is a joint inflammation caused by the accumulation of monosodium urate crystals, which triggers severe pain, swelling, redness, and limited movement. This condition can reduce quality of life and interfere with daily activities. One of the commonly used non-pharmacological therapies to help reduce pain intensity is cupping therapy, which works by improving microcirculation, removing stagnant blood, and decreasing inflammatory mediators. This study aims to describe complementary nursing care with the main problem of acute pain in patients with gout arthritis through the implementation of cupping therapy interventions. This research employed a descriptive analytical design using a case study method involving three gout arthritis patients who received cupping therapy once a week for three weeks. The instruments used included nursing care formats, observation sheets, physical examination, and pain intensity measurement using the Numeric Rating Scale (NRS). The implementation of cupping therapy showed a reduction in pain levels in all patients, where Mrs. W experienced a decrease from a pain score of 5 to 3, Mrs. D from 5 to 2, and Mrs. A from 5 to 3 after three sessions. Patients also reported feeling more relaxed and comfortable following the therapy. These results indicate that cupping therapy is effective in helping to reduce pain intensity in patients with gout arthritis.